Towards Elucidating Structure–Spectra Relationships in Rhamnogalacturonan II: Computational Protocols for Accurate 13C and 1H Shifts for Apiose and Its Borate Esters - Bharadwaj, Vivek S.; Westawker, Luke P.; Crowley, Michael F. (Frontiers in Molecular Biosciences, 2022)
Apiose is a naturally occurring, uncommon branched-chain pentose that is found in plant cell walls as part of the complex polysaccharide-Rhamnogalacturonan II (RG-II). The structural elucidation of the 3-D structure of RG-II by Nuclear Magnetic Resonance (NMR) spectroscopy is significantly complicated by apiose’s ability to cross-link via borate ester linkages to form RG-II dimers. Here, we develop a computational approach to gain insight into structure-spectra relationships of apio-borate complexes in an effort to complement experimental assignments of NMR signals in RG-II. Our protocol involves structure optimizations using density functional theory (DFT) followed by isotropic magnetic shielding constant calculations using the gauge-invariant atomic-orbital (GIAO) approach to predict chemical shifts. We evaluate the accuracy of 23 different functional-basis set (FBS) combinations with and without implicit solvation for predicting experimental 1H and 13C shifts of a methyl apioside and its three borate derivatives. The computed NMR predictions are evaluated on the basis of overall shift accuracy, relative shift ordering, and the ability to distinguish between dimer and monomer. We demonstrate that the consideration of implicit solvation during geometry optimizations in addition to the magnetic shielding constant calculations greatly increases the accuracy of NMR chemical shift predictions and can correctly reproduce the ordering of the 13C shifts and yield predictions that are on average within 1.50 ppm for 13C and 0.12 ppm for 1H shifts for apio-borate compounds.